THE STUDY OF STUDENTS’ DIFFICULTY IN OPERATING OBE THROUGH TPS METHOD: A CASE STUDY OF ALE (ELEMENTARY LINEAR ALGEBRA) COURSE - *, Fauziah; Wahyuni, Yusri (IJRDO- Journal of Educational Research, 2017)
This study aims to assess and analyze the students’ results of learning OBE Elementary Linear Algebra (ALE) using Think Pair Share learning model. This study was a classroom action research for this study aims to improve the learning outcomes of students who take mathematics education especially Elementary Linear Algebra course and improvements made continuously during the research.Subject of this study are 41 students of class A Faculty of Mathematics Education and Teaching who take Elementary Linear Algebra course in second semester of academic year 2015/2016. Data were analyzed by using simple statistics. Based on the analysis of the data, the study concluded that the learning outcomes of students increased from the first cycle to the second cycle and reach the target of this study is 70% that most of students in the class scored ≥ B.